2007
DOI: 10.1353/etc.2007.0000
|View full text |Cite
|
Sign up to set email alerts
|

Check in/ Check out: A Post-Hoc Evaluation of an Efficient, Secondary-Level Targeted Intervention for Reducing Problem Behaviors in Schools

Abstract: The Check in/ Check out (CICO) program was developed as a secondarylevel, targeted behavioral intervention in a three-tier preventative model of behavior support and has received empirical support as an effective way to reduce problem behaviors (Hawken & Horner, 2003; March & Horner, 2002). The purpose of the present study was to evaluate, post-implementation, the fidelity of implementation and effectiveness of the CICO program to reduce problem behavior when program training and implementation was managed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 6 publications
1
75
0
Order By: Relevance
“…The intervention is designed to (a) add structure to the school day, (b) provide regular opportunities for feedback, and (c) cultivate a relationship with an adult mentor in school. In addition to the evidence for direct behavior ratings in general (see Chafouleas, RileyTillman, & McDougal, 2002), Check-In/Check-Out, in particular, has been the focus of a number of intervention studies demonstrating its effectiveness in reducing problem behavior and increasing academic engaged time for students (Fairbanks et al, 2007;Filter et al, 2007;Hawken, 2006;Hawken, McLeod, & Rawlings, 2007;March & Horner, 2002;Todd, Campbell, Meyer, & Horner, 2008).…”
Section: Check-in/check-outmentioning
confidence: 99%
“…The intervention is designed to (a) add structure to the school day, (b) provide regular opportunities for feedback, and (c) cultivate a relationship with an adult mentor in school. In addition to the evidence for direct behavior ratings in general (see Chafouleas, RileyTillman, & McDougal, 2002), Check-In/Check-Out, in particular, has been the focus of a number of intervention studies demonstrating its effectiveness in reducing problem behavior and increasing academic engaged time for students (Fairbanks et al, 2007;Filter et al, 2007;Hawken, 2006;Hawken, McLeod, & Rawlings, 2007;March & Horner, 2002;Todd, Campbell, Meyer, & Horner, 2008).…”
Section: Check-in/check-outmentioning
confidence: 99%
“…These help to prevent problem behavior by prompting more appropriate behavior before a problem has occurred. Check-in/check-out (Fairbanks et al, 2007;Filter et al, 2007;Hawken et al, 2007;Hawken, Vincent, & Schumann, 2008), a frequently used Tier II intervention for students with disruptive or inattentive behavior, is a pointcard intervention that is aligned with the Tier I component of SWPBS (i.e., students earn points throughout the day for exhibiting behaviors aligned with the school's school-wide expectations). In check-in/check-out, students meet with an intervention coordinator at the beginning of the day to receive their point card and review behavioral expectations.…”
Section: Essential Features Of Tier II Interventionsmentioning
confidence: 99%
“…Examples include check and connect (Anderson, Christenson, Sinclair, & Lehr, 2004;Evelo, Sinclair, Hurley, Christenson, & Thurlow, 1996;, check-in/check-out (Fairbanks, Sugai, Guardino, & Lathrop, 2007;Filter et al, 2007;Hawken, MacLeod, & Rawlings, 2007;Todd, Campbell, Meyer, & Horner, 2008), and First Step to Success (Carter & Horner, 2007;Filter et al, 2007;Walker et al, 1998). Beyond these packaged interventions, there are numerous other strategies that have proven effective when implemented in a small group context.…”
mentioning
confidence: 99%
“…This process is simple to implement and would provide a good tracking measure to begin gathering data. Research has shown the effectiveness of the intervention and more importantly student acceptance of the process (Filter et al, 2007).…”
Section: The Second Tiermentioning
confidence: 99%
“…The goals of CICO are to increase the opportunities adults have for prompting students to engage in positive behavior, provide behavioral feedback to the student at predictable times throughout the day, developing a meaningful adultstudent relationship through positive interaction, and communicate behavioral challenges and successes with families daily (Filter et al, 2007;McIntosh et al, 2009). School counselors and special educators may have more flexibility built into their schedules when compared to classroom teachers and administrators making them more able to counsel students during classroom hours (McIntosh et al, 2009).…”
Section: Student Point Cardmentioning
confidence: 99%